Growth Pattern, Sex Ratio and Distribution of Humpback Fish (Hemisilurus heterorhynchus, Bleeker 1854) in the Flooded River Basin, Kampar Kiri, Riau Province - Roza Elvyra; Febrian Lailatul Fitri; Yusfiati Yusfiati; Khairijon Khairijon; Imelda Wardani (Jurnal Biologi Tropis, 2023)
Flood plain river is one of the characteristics of Riau Province. The difference between H. heterorhynchus fish and other species is its distinctive mouth and bent body. H. heterorhynchus is a fish with high economic value. These fish are often overfished, which can lead to a decline in the fish population in the future. Therefore, this research was carried out to be able to see the growth pattern, sex ratio and distribution of fish so that it can become the basis for information, cultivation and preservation of H. heterorhynchus. The number caught was 78 (56.67%) male fish and 36 (43.33%) female fish. The total body length of male fish is 19-41 and female fish is 19-50 cm, the total body weight of male fish is 40-310 g and female fish is 40-600 g. The allometric growth pattern of male and female fish was negative, with b values ​​of 2.8 (males) and 2.2 (females). Correlation analysis of H. heterorhynchus fish are r= 0.98 (male) and r=0.877 (female). The sex ratio of male and female fish is 1.16:1. Male fish are 19-22 cm and 23-26 cm (small fish), 27-30 cm and 31-34 cm (medium fish), and 35-38 cm and 39-42 cm (large fish). Female fish are 19-24 cm and 25-30 cm (small fish, 31-36 cm and 37-42 cm (medium fish), 43-48 cm and 49-54 cm (large fish).